Polystyrene microplastics induced nephrotoxicity associated with oxidative stress, inflammation, and endoplasmic reticulum stress in juvenile rats - Wang, Wanzhen; Guan, Jiafu; Feng, Yueying; Nie, Liju; Xu, Yuanyuan; Xu, Hengyi; Fu, Fen (Frontiers in Nutrition, 2023)
Unintended intake of microplastic particles has been demonstrated to exert adverse health effects, however, studies on relevant nephrotoxicity in juvenile mammals are lacking. Therefore, we investigated the potential nephrotoxicity of oral-exposed polystyrene microplastics (PSMPs) (1000 nm, 2.0 mg/kg/d) for 28 days in juvenile rats. Levels of oxidative stress, inflammation, and endoplasmic reticulum (ER) stress in kidneys were analyzed. Results revealed that PSMPs noticeably decreased the growth rate of bodyweight, and organ index of the kidney, cardiac, and ovary. The intestinal injury caused by PSMPs exposure was also observed, which was distinctly alleviated with N-acetyl-cysteine (NAC) and Salubrinal (Sal) treatment compared with the single PSMPs group. PSMPs caused histological lesions of the kidney via disrupting the serum blood urea nitrogen (BUN), creatinine (CRE), and pro-inflammatory mediators IL-1β, IL-6, and TNF-α. Furthermore, PSMPs exposure induced ER stress and inflammation presumably potentially mediated by oxidative stress in kidneys of rats. Eventually, PSMPs also promoted renal cells apoptosis, manifested as an obvious increase in the number of positive cells for the dUTP nick end labeling of Terminal deoxynucleotidyl transferase, which also can be confirmed by the elevated expression of genes associated with apoptosis Bcl-2, Bax, Caspase-12, Caspase-9, Caspase-3, and IHC score of Caspase-12 in the PSMPs group. Supplementation of NAC and Sal not only ameliorated the PSMPs-induced oxidative stress and ER stress but also the inflammation and apoptosis in the kidney. Collectively, this study suggested that PSMPs caused nephrotoxicity in juvenile rats potentially through oxidative damage and ER stress, which call for greater efforts to be taken on regulating the PSMPs ingestion in children.